Immobilized Lipase - Catalyzed Fish Oil Hydrolysis in Organic Solvent - Tyas Utami; Erryana Martati; Pudji Hastuti; Eni Harmayani (Indonesian Food and Nutrition Progress, 1999)
Immobilized lipase from Mucor miehei catalyzed the hydrolysis of cod liver oil in the presence of hexane was studied. The research was conducted to observe the effect of hexane on degree of hydrolysis, glyceride profile and EPA (eicosapentaenoic acid) and DHA (docosahexaenoic acid) contents. Enzymatic hydrolyses were carried out in a waterbath shaker at 50Â°C for 48 hours. Reaction mixtures contained of 1 g cod liver oil, hexane, Tris HCl buffer pH 7.5, and 10% (w/w oil) immobilized enzyme. Addition of various amount of hexane decreased the degree of hydrolysis and changed glyceride profile. Hexane to buffer ratio of 1:9 and 9:1 yielded 77% and 64% hydrolyses respectively. The results showed that degree of hydrolysis was affected by the oil concentration in the solvent system, not by the oil concentration in the overall system. It was observed that after hydrolysis, EPA dan DHA contents in the forms of glycreride and free fatty acid were higher in the addition of hexane than that of in the absence of hexane